2010
DOI: 10.1118/1.3476457
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of GEANT4 very low energy cross section models with experimental data in water

Abstract: The GEANT4-DNA physics models available in the GEANT4 toolkit have been compared in this article to available experimental data in the water vapor phase as well as to several published recommendations on the mass stopping power. These models represent a first step in the extension of the GEANT4 Monte Carlo toolkit to the simulation of biological effects of ionizing radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
364
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 434 publications
(372 citation statements)
references
References 63 publications
5
364
0
3
Order By: Relevance
“…For the "Penelope Physics List" the applicability limit is 100 eV. In the framework of the Geant4-DNA project (Incerti et al 2010, Bernal et al 2015, an alternative "Physics List" is available for liquid water simulating the dominant physical interactions of electrons down to thermalization energy (~25 meV). For this study we combine either the "Livermore" or "Penelope" "Physics List" for the GNP with the Geant4-DNA "Physics List" for the surrounding water.…”
Section: Introductionmentioning
confidence: 99%
“…For the "Penelope Physics List" the applicability limit is 100 eV. In the framework of the Geant4-DNA project (Incerti et al 2010, Bernal et al 2015, an alternative "Physics List" is available for liquid water simulating the dominant physical interactions of electrons down to thermalization energy (~25 meV). For this study we combine either the "Livermore" or "Penelope" "Physics List" for the GNP with the Geant4-DNA "Physics List" for the surrounding water.…”
Section: Introductionmentioning
confidence: 99%
“…DPKs were calculated with the new set of models at low incident electron energies (100 eV and 1 keV) considering either the Geant4-DNA default models or the newly proposed models. At 100 eV, it was observed that the default Geant4-DNA models lead to a long-tail DPK caused by the too low electronic excitation cross section available by default in Geant4-DNA, as underlined in [32,48]. At 1 keV, a good agreement is observed between both sets of models.…”
Section: Dose Point Kernelsmentioning
confidence: 83%
“…Since 2007, Geant4-DNA offers physics processes and models able to describe particle interactions in liquid water at nanometre scale [31][32][33]. This Package currently provides a complete set of models describing the event-by-event electromagnetic interactions of particles (electrons, protons and neutral hydrogen atoms, alpha particles including their charge states) with liquid water (as well as ionisation for a few ions -Li, Be, B, C, N, O, Si and Fe).…”
Section: Physics Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Geant4 is a general-purpose, open-source toolkit for the simulation of the passage of particles through matter that can, among other applications, also be used for track structure simulations by including the Geant4 Very Low Energy Extensions (Geant4-DNA) (Incerti et al, 2010).…”
Section: Interaction Cross Section Data In Ptra and Geant4-dnamentioning
confidence: 99%